Long‐term survival after heart transplantation for cardiac sarcoidosis. Issue 11 (27th June 2021) - McGoldrick, Matthew T.; Giuliano, Katherine; Etchill, Eric W.; Barbur, Iulia; Yenokyan, Gayane; Whitman, Glenn; Kilic, Ahmet
Abstract: Background: Cardiac sarcoidosis is an increasingly common indication for a heart transplant, but there is a paucity of knowledge with regard to long‐term outcomes following transplant. Methods: We utilized the Organ Procurement and Transplantation Network database to retrospectively analyze adult patients undergoing first‐time, single‐organ heart transplant between January 1999 and March 2020. Results: Of the 41, 447 patients that underwent heart transplant during the study period, 289 (0.7%) were transplanted for a primary diagnosis of restrictive cardiomyopathy due to cardiac sarcoidosis (RCM‐Sarcoidosis). RCM‐Sarcoidosis was associated with 33% reduced risk of mortality over 10 years compared to non‐RCM indications in a multivariable Cox proportional hazards model ( p  = .03). Ten‐year survival functions were improved among RCM‐Sarcoidosis compared to this reference group (73.4% [64.2%–80.6%] vs. 59.5% [58.8%–60.1%], p  = .002). Among patients transplanted after 1999 who had at least 10 years of follow‐up ( n  = 19, 489), median survival of RCM‐Sarcoidosis patients was 11.9 [8.3–14.6] years while that of non‐RCM patients was 9.9 [4.0–13.1] years. RCM‐Sarcoidosis was not associated with an increased risk of secondary outcomes such as graft failure, rejection, or infection. The incidence of retransplant was comparable between RCM‐Sarcoidosis and non‐RCM patients (1.38% vs. 1.50%, p  = .93). Conclusions: These data suggest that long‐term outcomes following transplant for cardiac sarcoidosis are favorable compared to heart transplant for other indications.